Recent advancements in cross-linked starches for food applications- a review - Sneh Punia Bangar; K.V. Sunooj; Muhammed Navaf; Yuthana Phimolsiripol; William Scott Whiteside (International Journal of Food Properties)
The industrial food applications of native starches are limited due to their limited resistance to shear, susceptibility to thermal decomposition, and high tendency for retrogradation. Cross-linking of starches adds intra and inter-molecular bonds at various locations in the starch molecule that result in the stability of the granule and enhance functional attributes. This process involves the use of various cross-linking agents such as sodium trimetaphosphate (STMP), sodium tripolyphosphate (STPP), epichlorohydrin (EPI), phosphorus chloride (POCl3), and citric acid, etc., to introduce covalent or non-covalent linkages between starch molecules. Cross-linked starch exhibits improved resistance to retrogradation, enhanced freeze-thaw stability, and increased stability during cooking, shearing, and processing, such as high or low temperatures and pH. This review paper offers an overview of cross-linking modifications, emphasizing their importance in addressing native starch limitations. It underscores the significance of selecting appropriate cross-linking agents to customize starch properties for specific applications. Furthermore, the paper discusses the properties and applications of cross-linked starches and delves into regulatory considerations regarding their use. Regulatory consideration for cross-linked starches has also been discussed. Cross-linking modifications offer a promising avenue to unlock the full potential of starch and expand its utility across a wide range of applications.